A case report of lupus erythematosus tumidus converted from discoid lupus erythematosus. Issue 16 (April 2018) - Chen, Xiaomei; Wang, Sheng; Li, Li
Abstract: Rationale: Lupus erythematosus tumidus (LET) is an uncommon type of cutaneous lupus erythematosus (CLE) that is rarely associated with other forms of lupus erythematosus. Patient concerns: We report a 62-year-old Chinese man presented with recurrent erythematous facial plaques for 1 year and a low-grade fever for 1 week. He had been diagnosed as discoid lupus erythematosus (DLE) 1 year before. Physical examination showed diverse lesions, including prominent swelling of the eyelids, a few erythematous, edematous plaques on the left forehead, face, and neck, and 2 hairless macules. The histopathologic findings reveal liquefaction degeneration of the basal cells, perivascular, and periadnexal infiltration of lymphocytes, and interstitial mucin deposition in the superficial, and deep dermis. Diagnoses: A diagnosis of LET was made on clinical and histological features. Interventions: The patient started treatment with prednisolone (1 mg/kg. d), combined with hydroxychloroquine (200 mg twice daily), and topical tacrolimus. Outcomes: The cutaneous lesions completely cleared after a period of 3 months. No adverse effects or clinical evidence of recurrence had been found during the 6-month follow-up period. Lessons: We report a case of LET converted from DLE with diverse lesions, unusual pathologic findings and slow response to the treatment of corticosteroids combined with hydroxychloroquine. We speculate that a continuous spectrum may include DLE, LET, and systemic lupus erythematosus (SLE), these 3 entities could potentially, convert between each other.